2012
DOI: 10.1080/01626620.2012.642282
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Efficacy: How Teachers Rate Themselves and How Students Rate Their Teachers

Abstract: The purpose of this investigation was to compare how teachers rate themselves with how students rate their teachers on the Teacher Efficacy the External Influences Scale, a scale designed to assess teachers' efficacy in the area of classroom organization and discipline. The participants in this study were seventh-and eighth-grade teachers and their students in a middle school located in a metropolitan area of a midsized, midwestern community in the United States. There were 710 students and 18 teachers partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Another aspect that refers to the self-efficacy is connected to classroom management. Here, too, like in other studies (Bordelon et al, 2012) the findings show that the graduates have a medium to high selfefficacy to introduce clear norms of discipline and working procedures in their class. The TSR measure has given medium-high results.…”
Section: The Self-efficacy and Contributions That Influence The Way Osupporting
confidence: 86%
See 1 more Smart Citation
“…Another aspect that refers to the self-efficacy is connected to classroom management. Here, too, like in other studies (Bordelon et al, 2012) the findings show that the graduates have a medium to high selfefficacy to introduce clear norms of discipline and working procedures in their class. The TSR measure has given medium-high results.…”
Section: The Self-efficacy and Contributions That Influence The Way Osupporting
confidence: 86%
“…Self-efficacy of teachers refers to their ability to carry out specific teaching/learning tasks, in their classes (Dellinger et al, 2008), and was defined as an ability to influence their students' achievements, including those with learning difficulties (Tschannen-Moran & Wolfolk-Hoy, 2001). An important component of self-efficacy of teachers is their sensation about classroom management and discipline (Bordelon, Phillips, Parkison, Thomas & Howell, 2012), and their ability to involve 'challenging' students. Success or failure in this domain, determines the development of efficacy of the teacher (Cornelious-White & Harbaugh, 2012).…”
Section: The Personal and Collective Contexts Of Self-efficacy Of Teamentioning
confidence: 99%
“…The study on developing teacher candidates'Self-efficacy by Black (2015) has relation with the literature on teacher self-efficacy, teacher candidates who perceived themselves as confident in their lesson plan reflections and summative reflections, created enabling learning environments for their students (Bordelon, Phillips, Parkison, Thomas, & Howell, 2012;Tschannen-Moran & Hoy, 2001;Yost, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…They are more committed to their professional development, and are more likely to positively influence their teaching practices and students' performance (Allinder, 1994;Chacón, 2005). They use multiple strategies to keep students engaged in their learning, and use active and progressive methods (e.g., creating a supportive learning environment) when interacting with students (Bordelon, Phillips, Parkison, Thomas, & Howell, 2012;Chacón, 2005;Gorozidis & Papaionnou, 2011). Gibson and Dembo (1984) also found a significant relationship between TSE and the teaching methods used.…”
mentioning
confidence: 95%
“…Recent findings showed that teachers' self-efficacy beliefs played a crucial role in affecting and sustaining their commitment to their teaching practices, and job satisfaction (Caprara, Barbaranelli, Borgogni, & Steca, 2003). Recently, Bordelon et al (2012) showed in a study about the influence of TSE on students' performance that TSE has a positive influence on students' behavior. In addition, such high self-efficacy teachers may gain better results from low achievement students, and compensate for students' negative home experiences through good teaching.…”
mentioning
confidence: 97%